2020
DOI: 10.1002/chem.202002143
|View full text |Cite
|
Sign up to set email alerts
|

Handling (Nano)Silver as Antimicrobial Agent: Therapeutic Window, Dissolution Dynamics, Detection Methods and Molecular Interactions

Abstract: Silver is an antimicrobial agent well known since antiquity. With the emergence of multiresistant bacteria, it has come back into the focus of research, and ionic as well as nano‐sized silver have been studied in vitro and in vivo. The results are controversial, silver being discussed as the “silver bullet” or a “wolf in sheep's clothing”. A thorough search of literature from chemistry, materials and environmental science, biology and medicine led to this Review which summarizes the potential use of silver and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 196 publications
(251 reference statements)
2
32
0
Order By: Relevance
“…This difference between the elimination capacities of these tested bacteria was due to the fact that the composition of their membranes is very different, conferring greater resistance to the Gram + S. aureus. For the elimination of C. albicans, that is, a more complex cellular constitution, the PP/3AP composite had contact elimination of 99% at the maximum time (3 days).…”
Section: Results and Discussionmentioning
confidence: 99%
“…This difference between the elimination capacities of these tested bacteria was due to the fact that the composition of their membranes is very different, conferring greater resistance to the Gram + S. aureus. For the elimination of C. albicans, that is, a more complex cellular constitution, the PP/3AP composite had contact elimination of 99% at the maximum time (3 days).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Silver has been well known for its antibacterial properties for many years (its beneficial role in the treatment of infection dates back to at least 4000 B.C.) and its mechanism of action is one of the best understood [24,25]. Silver ions mainly affect thiol groups (-SH), present in bacterial proteins' structure, by substituting hydrogen atoms and the arising of S-Ag binding.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that eukaryotic cells are more tolerant of Ag than prokaryotic cells. , In prokaryotes, important biochemical pathways such as the respiratory chain or DNA replication are located at the cytoplasmic membrane, while the mitochondria and nucleus of eukaryotic cells are protected in cellular organelles . Therefore, the difference between the cytotoxic and the antibacterial concentrations of Ag can be used as a therapeutic window for antibacterial applications …”
Section: Introductionmentioning
confidence: 99%
“…13 There-fore, the difference between the cytotoxic and the antibacterial concentrations of Ag can be used as a therapeutic window for antibacterial applications. 14 Nevertheless, the applications of Ag are controversial. 15 Some researchers found that Ag-containing dressings delayed wound healing 16,17 while others confirmed that Ag-containing dressings promoted wound healing.…”
Section: Introductionmentioning
confidence: 99%